Trajectories of attention‐deficit/hyperactivity disorder dimensions in adults. (26th May 2017) - Karam, R. G.; Rovaris, D. L.; Breda, V.; Picon, F. A.; Victor, M. M.; Salgado, C. A. I.; Vitola, E. S.; Mota, N. R.; Silva, K. L.; Meller, M.; Rohde, L. A.; Grevet, E. H.; et al.
Abstract : Objective: There is a lack of available information on the trajectories of attention‐deficit/hyperactivity disorder (ADHD) dimensions during adulthood. This study investigates the course and the predictors of change for each ADHD domain in a clinical sample of adults with ADHD. Method: Adults with ADHD ( n = 344) were followed up for 7 years, with a final retention rate of 66.0%. Trajectories of inattention, hyperactivity, and impulsivity and their potential predictors were examined. Results: On average, symptoms declined in all ADHD domains during follow‐up. Despite this, rises in inattentive, hyperactive, and impulsive symptoms were observed in approximately 13%, 25%, and 17% of patients respectively. Different predictors influenced the trajectory of each ADHD dimension. Oppositional defiant disorder and social phobia were associated with the maintenance of symptoms, while alcohol use disorder was associated with both maintenance and rise of symptoms. Conclusion: Unexpectedly, a rise in the symptoms after 7 years was not uncommon in adults with ADHD. Prevalent comorbidities have the potential to influence the neurodevelopment and the trajectory of ADHD. Therefore, such predictors should be investigated in population cohorts to better characterize the course of ADHD. Additionally, these findings may be relevant in prevention studies and in strategies for ADHD treatment.